Analisis Penyebab Tingginya Kasus Penyalahgunaan Narkoba di Kabupaten Aceh Utara - Sukmawati, Cut; Murniati, Murniati; Yunanda, Rizki; Sakdiah, Sakdiah; Safrina, Safrina (Aceh Anthropological Journal, 2023)
The issue of drug abuse and illicit trafficking is increasing every year. North Aceh District of Aceh Province is one of the districts with a high number of drug abuse cases, as in 2018 there were 124 cases of drug abuse and in 2019 there were 96 cases. This article describes the reality of the causes of high drug abuse cases in North Aceh District. The study was conducted in North Aceh District, Aceh, Indonesia, using qualitative methods in the research process. Observation, interviews and document utilization were used to collect data on the causes of high drug abuse in North Aceh district. The data collected was then classified, arranged in patterns, organized, interpreted, given meaning and concluded. This study found that there are different views, from the North Aceh local government, which is still not fully committed to the implementation of P4GN facilitation so that there is still high drug abuse, from the BNNK and North Aceh Police. The causes of the high number of cases of drug abuse and illicit trafficking in North Aceh Regency are lack of public awareness, non-existent rehabilitation facilities, the number of drug entry points into North Aceh, the existence of individual factors that cannot say NO to drugs. The influence of environmental factors (family, school and socialization), and the absence of local regulations and P4GN Action Plans.Abstrak: Permasalahan penyalahgunaan dan peredaran gelap narkotika setiap tahunnya semakin mengalami peningkatan. Kabupaten Aceh Utara  Provinsi Aceh merupakan salah satu Kabupaten dengan tingginya jumlah kasus penyalahgunaan narkotika, seperti halnya tahun 2018 ada 124 kasus penyalahgunaan narkoba dan pada tahun 2019 ada 96 kasus. Artikel ini mendeskripsikan realitas penyebab tingginya kasus penyalahgunaan narkoba di Kabupaten Aceh Utara. Studi yang dilakukan di Kabupaten Aceh Utara, Aceh, Indonesia ini menggunakan metode kualitatif dalam proses penelitiannya. Observasi, wawancara (interview) dan pemanfaatan dokumen digunakan untuk mengumpulkan  data  tentang penyebab masih tingginya penyalahgunaan narkotika di kabupaten Aceh Utara. Data yang berhasil dikumpulkan kemudian diklasifikasikan, disusun dalam pola-pola, diorganisasikan, ditafsirkan, diberi makna dan kesimpulan. Penelitian ini menemukan bahwa ada perbedaan pandangan, dari Pemda Aceh Utara masih belum berkomitmen penuh untuk implementasi Fasilitasi P4GN sehingga masih tingginya penyalahgunaan narkoba, dari pihak BNNK dan Polres Aceh Utara. Penyebab masih tingginya kasus penyalahgunaan dan peredaran gelap narkoba di Kabupaten Aceh Utara yaitu kurangnya kesadaran masyarakat, fasilitasi rehabilitasi yang belum ada, banyaknya jalur masuk narkoba ke Aceh Utara, Adanya faktor individu yang tidak bisa berkata TIDAK pada narkoba. Adanya pengaruh faktor lingkungan (keluarga, sekolah dan pergaulan), dan belum adanya Peraturan daerah dan Rencana Aksi P4GN.